PERUBAHAN POLA STRATEGI PEMASARAN KERAJINAN TANGAN DI SINGARAJA PADA MASA PANDEMI COVID-19 - Febri Purnama Sari, Desak Made; Risa Indriyani, Ni Kadek (E-Jurnal Manajemen; Vol 11 No 1 (2022), 2022)
The change in the pattern of marketing strategies for handicrafts in Singaraja during this pandemic, aims to find out the changes in strategy made by handicraftsmen in Singaraja during the COVID-19 pandemic. This research is descriptive qualitative, using data collection methods of observation, interviews, and documentation with five selected informants. The location of this research is in Tigawasa Village because Tigawasa Village is famous for its handicrafts. The results of this study are, the craftsmen in Tigawasa Village make changes to their marketing strategy using digital marketing using social media applications such as Facebook, Instagram, and WhatsApp. In addition, craftsmen also use e-commerce, namely the Shopee application. This study also found that, the craftsmen in Tigawasa Village used the 4P marketing mix strategy and implemented marketing strategic steps, namely market segmentation, determining market targets, and market positioning. Keywords: Marketing Strategy,  Digital Marketing, 4P Marketing Mix,  Steps of Marketing Strategy